Fort San Juan and the Limits of Empire : Colonialism and Household Practice at the Berry Site - Moore, David G. (David Gilbert), 1951-; Rodning, Christopher Bernard; Beck, Robin A. (Ripley P. Bullen series., 2015)
Established in 1566 by Spanish conquistador Juan Pardo, Fort San Juan is the earliest known European settlement in the interior United States. Located at the Berry site in western North Carolina, the fort and its associated domestic compound stood near the Native American town of Joara, whose residents sacked the fort and burned the compound after only eighteen months. Drawing on archaeological evidence of architecture, food, and material culture, as well as newly discovered accounts of Pardo's expeditions, the contributors to this volume explore this borderland location at the northern frontier of Spain's long reach. They piece together the fragments of the colonial encounter between Pardo's thirty soldiers and the people of Joara to chronicle the deterioration in Native American-Spanish relations that sparked Joara's revolt. Fort San Juan and the Limits of Empire offers critical insight into the nature of early colonial interactions.